Variasi Morfometrik Kepiting Biola (Uca sp.) di Cagar Alam Tanjung Panjang, Kecamatan Randangan, Gorontalo - Ismiyati Uno; Abubakar Sidik Katili; Zuliyanto Zakaria (Jambura Edu Biosfer Journal, 2019)
The research was aimed at explaining the morphometric ratio of fiddler crab (Uca sp.) based on the difference among the population in Tanjung Panjang Nature Preserve. The technique of data collection was exploration with quantitative descriptive approach. The data analysis test applied average test and T- test. Findings revealed that the variation of the characteristics of morphometric of the two population was different on the characteristics of major claws propondus (2,55±0,16 mm) with the highest variation was found in station II (0,75±0,09 mm). The morphometric characteristic variations which were significantly different between the two population were carapace, major claws, and mouth. The variations among the population were clearly, seen through carapace posterior width, major claws propondus, major claws dactylus major claws and mouth length.